Anticoccidial activity of novel triazine compounds in broiler chickens - Zhang, Min; Li, Xueyan; Zhao, Qiping; She, Rufeng; Xia, Suhan; Zhang, Keyu; Zhang, Lifang; Wang, Xiaoyang; Wang, Mi; Liu, Yingchun; Wang, Chunmei; Zhang, Jie; et al. (Veterinary parasitology, 2019)
•The anticoccidial efficacy of AZL and EZL were determined for the first time.•The activity of AZL and EZL was lower than that of the parent nitromezuril.•EZL had higher sensitivity against two field Eimeria isolates.•The position of C4 substituent of phenol of EZL may have important biological functions. The objective of present studies was to evaluate and compare the anticoccidial activity of triazine compounds in broiler chickens infected with E. tenella, E. necatrix, E. acervulina, E. maxima, and two field mixed Eimeria species. The anticoccidial efficacy was evaluated using the anticoccidial index (ACI). The results showed that Aminomizuril (AZL) and Ethanamizuril (EZL) were active metabolites of nitromezuril, which demonstrated excellent effectiveness against E. tenella, E. necatrix, E. acervulina, E. maxima, and the field Eimeria isolates in broiler chickens at a dosage of 10 mg/kg in feed. The anticoccidial activities of AZL and EZL at dose 10 mg/kg were roughly equivalent to the parent nitromezuril at a dosage of 3 mg/kg in feed. The decrease in metabolite anticoccidial activity is probably due to an increasing polarity of compounds in the metabolic processes. The sensitivity of two field Eimeria isolates to triazines EZL, diclazuril and toltrazuril was tested using 4 indices including anticoccidial index (ACI), percent of optimum anticoccidial activity (POAA), reduction of lesion scores (RLS) and relative oocysts production (ROP). Results showed that the sensitivity of EZL treatment against the two field Eimeria isolates were relatively superior to that of diclazuril and toltrazuril treatment. The field Eimeria isolates from Gansu Province was determined to be slightly, moderately and highly resistant to EZL, diclazuril and toltrazuril respectively. The field Eimeria isolates from Zhejiang Province was slightly, highly and slightly resistant to EZL, diclazuril and toltrazuril respectively. The results above indicated that the anticoccidial activity of metabolites was lower than that of the parent nitromezuril and there was partial cross-resistance among triazines EZL, diclazuril and toltrazuril. However the field Eimeria isolates had higher sensitive to EZL than the triazines diclazuril and toltrazuril. It was suggested that the site of C4 substituents of phenol of triazine anticoccidials may have important biological functions and the metabolite EZL would be a potential novel anticoccidial agent worthy of more attention.